The Tip60/Ep400 chromatin remodeling complex impacts basic cellular functions in cranial neural crest-derived tissue during early orofacial development - Gehlen-Breitbach, Sebastian; Schmid, Theresa; Fröb, Franziska; Rodrian, Gabriele; Weider, Matthias; Wegner, Michael; Gölz, Lina (International Journal of Oral Science, 2023)
The cranial neural crest plays a fundamental role in orofacial development and morphogenesis. Accordingly, mutations with impact on the cranial neural crest and its development lead to orofacial malformations such as cleft lip and palate. As a pluripotent and dynamic cell population, the cranial neural crest undergoes vast transcriptional and epigenomic alterations throughout the formation of facial structures pointing to an essential role of factors regulating chromatin state or transcription levels. Using CRISPR/Cas9-guided genome editing and conditional mutagenesis in the mouse, we here show that inactivation of Kat5 or Ep400 as the two essential enzymatic subunits of the Tip60/Ep400 chromatin remodeling complex severely affects carbohydrate and amino acid metabolism in cranial neural crest cells. The resulting decrease in protein synthesis, proliferation and survival leads to a drastic reduction of cranial neural crest cells early in fetal development and a loss of most facial structures in the absence of either protein. Following heterozygous loss of Kat5 in neural crest cells palatogenesis was impaired. These findings point to a decisive role of the Tip60/Ep400 chromatin remodeling complex in facial morphogenesis and lead us to conclude that the orofacial clefting observed in patients with heterozygous KAT5 missense mutations is at least in part due to disturbances in the cranial neural crest.
CRIS-Team Scopus Importer:2023-04-21